ALIENATED FEMALE ANGLO-IRISH YOUTH IN ELIZABETH BOWEN’S THE LAST SEPTEMBER - Nita, Ida Ayu Eka Vania Cahya; Priyatna, Aquarini; Adipurwawidjana, Ari Jogaiswara (Universitas Padjadjaran, 2025)
Elizabeth Bowen’s The Last September (1929), a novel about an Anglo-Irish gentry family in Danielstown, Cork in the middle of the war for Irish independence from England, portrays the fate of the youths of the Anglo-Irish. By referring to Warhol’s feminist narratological approach, this research aims to display the portrayal of Lois Farquar’s as a representation of a female member of the Anglo-Irish society. The Last September, as a modernist novel, portrays Lois’s gendered experience through actions, dialogue and narrations. Lois Farquar, teenage protagonist of the novel, is depicted to be grappling with her own struggle with self-realization and the expectations set by her Anglo-Irish family. Lois’s struggle with her identity is, in part, a consequence of the repression and alienation she and fellow members of the Anglo-Irish society experience, stunting the development of Lois’s identity and agency. Thus, we propose that the novel, with its modernist narrative that centers around female Anglo-Irish interiority, presents Lois, and the youths of the Anglo-Irish, as aliens frozen in time, lacking the ability to inherit their legacy or undergo transformation.